The quality of details when children and youths with intellectual disabilities are interviewed about their abuse experiences - Cederborg, Ann-Christin (Scandinavian journal of disability research, 2011)
The question for this study was to further understand how children and youths with intellectual disabilities (IDs) provide central and peripheral details when interviewed about their abuse experiences. Through a quantitative method we examined police officers’ first formal investigative interviews with 32 children and youths with IDs. We analyzed the details they reported about abuse in relation to types of questions asked. The findings showed that few open-ended invitations were used and that a large number of option-posing questions were asked. The children and youths tended to agree with option-posing and suggestive statements but were nonetheless able to report important information about their abuse experiences without the ‘help’ from these potentially contaminating questions. The results of this study are limited because of the selective nature of the sample and that we did not have access to complete information about the participants specific diagnosis. Although it shows that police officers need to provide children and youths with IDs greater opportunities to report details using open-ended invitations. If they do not develop their responses when asked open-ended invitations they may be asked open directive questions to facilitate the elicitation of both central and peripheral information